SOCIO-PHILOSOPHICAL ASPECTS OF SOME FOREIGN COUNTRIES' EXPERIENCE ON CRIMINAL PUNISHMENT (Scientific journal of the Fergana State University, 2023)
The legal signs of several forms of crime and their importance in the appointment of punishment have been studied in detail. The influence of the legal significance and forms of several crimes on the determination of issues related to the appointment of punishment, early release from liability and punishment and the legal consequence after serving the sentence was studied, approaches to this concept were studied and author's definitions were developed. In turn, the absence of a single approach to the concept of several crimes at the moment, its lack of a clear scientific and legal definition, the presence of problems in the appointment of punishment for several forms of crime and the need to develop a single definition in this regard, the need to abandon the norm of repeated crime, give a new definition of the concept, the manifestation of the legal consequence of the norm of prescribing punishment for a recidivism in the absence of exemption from punishment and liability of a person is studied separately.